Pengembangan Media Pop-Up Book dalam Materi Sakramen-Sakramen Gereja pada Siswa Kelas VIII - Herkulanus Pongkot; Hugo Theo Kurniason; Apri Kurniawan (Departement of Mathematics Education, 2023)
This research is research and development. The resulting product is a pop-up book learning media material for the Church's sacraments. The development steps use the modified Borg and Gall, namely potential and problem identification, data collection, information gathering, product design, design validation, design revision, testing, and product revision. Products are validated by media experts and material experts. Material experts give a validation value of 92% which is categorized as very good, while media experts provide a validation value of 93.3% which is categorized as very good. After being validated, the product was tested in class VIII SMP Negeri 07 Tayan Hilir. Students are given a response questionnaire to the pop-up book media to see student responses to the products that have been made. As a result, student responses reached a score of 91.12% which was categorized as very good.